2021
DOI: 10.1039/d0se01251c
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer characteristics and energy penalty analysis of MEA regeneration process in packed column

Abstract: The high energy consumption of MEA regeneration process is the biggest challenge for the application of CO2 capture by the monoethanolamine (MEA) solution. Therefore, it is of significance to determine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The thermodynamic model describes the steam characteristics in turbine, condenser and regenerative heating system under off-design conditions. For the turbine, Flugel formula [32] is mainly used,…”
Section: Mathematical Models Of Thermal-fluid Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic model describes the steam characteristics in turbine, condenser and regenerative heating system under off-design conditions. For the turbine, Flugel formula [32] is mainly used,…”
Section: Mathematical Models Of Thermal-fluid Processmentioning
confidence: 99%
“…This model has definite physical meaning, but due to the mechanism of entransy theory, the optimization model is very complex. On the other hand, Goodarzi and Amooie [31] tried to solve this problem in mathematical way, they used genetic algorithm to calculate the optimal water distribution, but their study was only about the cooling tower itself; this caused a lack of practical significance in a way because the cooling tower was just a part of the whole power generating system, the optimal thermo-flow performance of a single unit did not correspond to the optimal operation point of a system [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…dm d /dt is the mass flow rate transferred to the air by evaporation, which explains the evaporation rate of droplet and determined by the density variation between the droplet gas-liquid surface and oversaturated steam in the flow duct. dm d /dt is described as follows [28,29]:…”
Section: Discrete Phase (Water Droplets)mentioning
confidence: 99%
“…According to the assumption mentioned earlier that all the atomized droplets have independent characteristic and remain spherical shape during the evaporation process, it is concluded that the changes on the droplet velocity and direction are only caused by drag force and gravity. The motion equation of a single droplet is described as [36,37],…”
Section: Discreate Phase (Atomized Droplets)mentioning
confidence: 99%